Inter-annual and Intra-annual variability in ice flow of Hubbard Glacier, Alaska - van Wychen, Wesley; Wendleder, Anna; Bayer, Courtney (2021)
Quantifying and characterizing variability in the motion of tidewater glaciers is important for calculating total mass loss (iceberg production) to the ocean, refining estimates of global sea level rise, identifying the processes that control ice motion at seasonal and multi-annual time scales and for creating datasets that can be used to calibrate and validate the outputs of ice flow models. Here, we combine pre-derived velocity maps (i.e. from optical and SAR imagery available throughout openly available data portals) with newly-derived velocity maps determined from offset tracking of TerraSAR-X imagery to create a robust record of ice motion for Hubbard Glacier, one of the largest and fastest flowing glaciers in Alaska. This record allows us to describe the evolving velocity structure of this glacier at annual resolution from 1985 to 2018 and at seasonal resolution from 2014 to 2021. The annually resolved results (1985-2018) indicate that Hubbard Glacier has generally slowed over the last three decades in the lower ~30 km of the glacier, while the seasonally resolved results (2014-2021) show that the lower ~15 km section of the glacier undergoes clear oscillations between slower and faster flow throughout the year. Collectively, these results provide a comprehensive record of the dynamics of Hubbard Glacier and showcase the utility of the continuous collection of remote sensing datasets to understand how glaciers are responding to a warming climate.